SAT0467 LOW SERUM OSTEOCALCIN LEVELS ARE ASSOCIATED WITH THE PRESENCE OF DIABETES MELLITUS IN GLUCOCORTICOID TREATED PATIENTS. (2nd June 2020) - Florez, H.; Hernández-Rodríguez, J.; Carrasco, J. L.; Prieto-González, S.; Filella, X.; Monegal, A.; Guañabens, N.; Peris, P.
Abstract : Background: Increasing evidence indicates that osteocalcin (OC) is involved in the regulation of glucose homeostasis. Glucocorticoid (GC) treatment is associated with impaired osteoblast function and decreased OC levels and also with the development of CG-induced diabetes mellitus (GIDM). However, whether decreased OC levels in GC-treated subjects contribute to GIDM is not well known. Objectives: To analyse whether OC levels in GC-treated patients are associated with the presence of GIDM. Methods: 127 patients (aged 62±18years, 63% women) on GC treatment for autoimmune diseases (≥5mg/day, >3 months) were included. Clinical and anthropometric data were analysed, including the GC dose and treatment duration, presence of GIDM, fragility fractures, densitometric osteoporosis and bone formation (OC, bone alkaline phosphatase [BAP], PINP) and resorption markers (urinary NTX, serum CTX). The cut-offs of each bone marker for the presence of GIDM were estimated and optimized with the Youden index and included in the logistic regression analysis (adjusted for BMI, age and GC doses). Results: 17.3% of patients presented GIDM. Diabetic subjects were older (70.5±12.2 vs. 59.6±18.4, p=0.001) and had a higher BMI than non-diabetics (30±5.2 vs. 26±4.2, p=0.002). No differences were observed in GC dose or duration or in the presence of vertebral fractures. Diabetics showed lower levels of OC (7.57±1.01 vs. 11.56±1; p<0.001), PINP (21.48±1.01 vs. 28.39±1; p=0.0048), NTx (24.91±1.01 vs. 31.7±1; p=0.036) and CTX (0.2±1.01 vs. 0.3±1; p=0.0016) with similar BAP values. The best discriminating cut-offs for GIDM presence were: <9.25ng/mL for OC, <24ng/mL for PINP, <27.5nMol/mM for NTX and <0.25ng/mL for CTX. On multivariate analysis OC (<9.25) was the only marker related to the presence of GIDM (OR 6.1; CI95% 1.87-19.89; p=0.001). Conclusion: Decreased OC levels in GC-treated patients are associated with an increased risk of GIDM, a finding that was not observed with other bone turnover markers, further confirming the involvement of OC in the glucose homeostasis regulation in this entity. Disclosure of Interests: None declared